Laminate sheet for lid, lid, food packaging container and packaged food
Patent Information
- Application Number
- JP2023100858
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2025-01-08
AI Technical Summary
【0027】 本発明によれば、食品用包装容器に用いられ、紙基材を含んで環境負荷が小さく、耐ブロッキング性とヒートシール性を両立した蓋体が提供される。
Smart Images

Figure 2025001339000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated sheet for a lid, a lid, a food packaging container, and a packaged food. [Background technology]
[0002] In recent years, the demand for pre-cooked or pre-processed chilled and frozen foods sold at convenience stores and supermarkets has been growing, supported by advances in distribution and freezing / refrigeration technology, in addition to changes in household structure and lifestyle due to the trend toward nuclear families. At the same time, the demand for packaging containers for chilled and frozen foods is also growing.
[0003] Meanwhile, as efforts are being made to reduce plastic waste, there is an increasing demand for food packaging containers that use paper, a renewable resource with a low environmental impact, as the base material. There is also a demand for paper packaging containers that use paper as the base material for packaging containers that hold chilled and frozen foods.
[0004] Some packaging containers include a container body with an opening and a lid that covers the opening. When the lid has a heat seal layer, the lid is sealed to the container body by heat sealing to provide hermetic packaging. In order to prevent deterioration or leakage of the contents during transportation and storage of the packaged food, the lid is required to have heat sealability.
[0005] In addition, when a lid laminate sheet used for a lid is continuously manufactured, the sheet is manufactured while being wound into a roll and stored in that state. When the lid laminate sheet has a heat seal layer, there is a problem that the heat seal layer coated surface of the wound sheet sticks to the back surface of the sheet in contact with the heat seal layer coated surface, causing peeling (blocking). Therefore, a lid laminate sheet having a heat seal layer is required to have good blocking resistance in addition to heat sealability (for example, see Patent Documents 1 to 6). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2022-11700 [Patent Document 2] JP 2023-10964 A [Patent Document 3] JP 2023-10963 A [Patent Document 4] JP 2022-175023 A [Patent Document 5] JP 2022-130266 A [Patent Document 6] Patent Publication No. 2022-48970 Summary of the Invention [Problem to be solved by the invention]
[0007] In order to achieve both sealing properties and easy opening properties in the heat seal layer, a sealant film called an easy peel sealant is preferably used. From the viewpoint of reducing the environmental load, it is preferable that the heat seal layer is thin. Heat seal varnish forms a heat seal layer by coating a coating liquid on a substrate, and it is possible to significantly reduce the thickness compared to a sealant film. For this reason, it is preferable to use a coating agent such as varnish to form the sealant layer instead of a sealant film.
[0008] Coating agents such as heat seal varnish are more susceptible to blocking than sealant films, due to the relatively low molecular weight of the resin component. For this reason, a technology has been disclosed in which a particulate material is blended into the coating as an anti-blocking agent to form protrusions on the surface of the heat seal layer, thereby reducing the contact area between the heat seal layer and the layer in contact with it when wound into a roll, thereby suppressing blocking (see, for example, Patent Documents 2 and 3, etc.).
[0009] However, particulate materials used as antiblocking agents generally do not have the ability to seal to adherends, and therefore have the problem that the sealing ability is easily reduced, contrary to the improvement of blocking resistance.
[0010] An object of the present invention is to provide a lid for use in food packaging containers, which contains a paper base material, has a small environmental impact, and has both blocking resistance and heat sealability. [Means for solving the problem]
[0011] According to one aspect of the present invention, there is provided a laminated sheet for a lid used for a lid of a food packaging container having a container body with an opening and a lid covering the opening, the laminated sheet comprising, in this order, a water-resistant functional layer, a paper base material, a support layer, and a heat seal layer, The heat seal layer contains an ethylene-vinyl acetate copolymer and a fatty acid amide additive, and may further contain particles, provided that when the particles are contained, the content of the particles in the heat seal layer is 11% by mass or less, and The heat seal layer provides a laminated sheet for a lid having a peak adhesive strength in the range of -28 gf to 0 gf as measured by a probe tack test.
[0012] According to another aspect of the present invention, there is provided the laminate sheet for a lid according to the above aspect, wherein the particles have an average particle size of 40 μm or less.
[0013] According to yet another aspect of the present invention, there is provided a laminate sheet for a lid body relating to any of the above aspects, in which, when layers other than the paper base material contained in the laminate sheet for a lid body are classified into layers made of plastic and other layers, the mass of the paper base material is greater than the total mass of the layers made of plastic and the total mass of the other layers.
[0014] According to yet another aspect of the present invention, there is provided a laminate sheet for a lid body relating to any of the above aspects, further comprising a printed layer between the water-resistant functional layer and the paper base material, and further comprising a gas barrier layer between the printed layer and the heat seal layer.
[0015] According to yet another aspect of the present invention, there is provided the laminate sheet for a lid according to any one of the above aspects, wherein the paper base material is a coated paper having a coating layer on at least one surface thereof.
[0016] According to yet another aspect of the present invention, there is provided a laminate sheet for a lid body according to any one of the above aspects, wherein the ethylene-vinyl acetate copolymer contained in the heat seal layer has a glass transition temperature of -40°C or higher and a melting point within the range of 40 to 100°C.
[0017] According to yet another aspect of the present invention, there is provided the laminate sheet for a lid according to any one of the above aspects, wherein the heat seal layer is a cured film of a coating film made of a heat seal varnish.
[0018] According to still another aspect of the present invention, there is provided the laminate sheet for a lid according to any one of the above aspects, wherein the heat seal layer contains a secondary amide as the fatty acid amide-based additive.
[0019] According to yet another aspect of the present invention, there is provided the laminate sheet for a lid according to the above aspect, wherein the heat seal layer contains N-oleyl palmitamide as the secondary amide.
[0020] According to yet another aspect of the present invention, there is provided the laminate sheet for a lid according to any one of the above aspects, wherein the heat seal layer has a thickness within a range of 2.5 to 5.5 μm.
[0021] According to yet another aspect of the present invention, there is provided a lid comprising the lid-forming laminate sheet according to any one of the above aspects.
[0022] According to yet another aspect of the present invention, there is provided a food packaging container comprising a container body having an opening and a lid body on the side covering the opening, wherein the support layer is disposed between the paper base material and the internal space of the food packaging container.
[0023] According to yet another aspect of the present invention, there is provided a food packaging container according to the above aspect, wherein the container body has a flange around the opening, and the lid body is heat-sealed to the flange via the heat seal layer.
[0024] According to yet another aspect of the present invention, there is provided a food packaging container relating to any of the above aspects, wherein the internal space of the food packaging container is filled with a mixed gas including oxygen gas, nitrogen gas, and carbon dioxide gas.
[0025] According to yet another aspect of the present invention, there is provided a food packaging container according to any of the above aspects, wherein the food packaging container is a chilled food packaging container or a frozen food packaging container.
[0026] According to yet another aspect of the present invention, there is provided a packaged food comprising a food packaging container according to any one of the above aspects and food contained in the food packaging container. Effect of the Invention
[0027] According to the present invention, there is provided a lid for use in food packaging containers, which contains a paper base material, has a small environmental impact, and has both blocking resistance and heat sealability. [Brief description of the drawings]
[0028] [Figure 1] 1 is a partial cross-sectional view illustrating an example of a lid laminate sheet according to a first embodiment of the present invention. [Diagram 2] FIG. 4 is a cross-sectional view showing a food packaging container according to a third embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. The embodiment described below is a more specific embodiment of any of the above aspects. Elements having the same or similar functions are given the same reference numerals, and duplicated descriptions will be omitted.
[0030] [First embodiment] FIG. 1 is a partial cross-sectional view that illustrates an example of a lid laminate sheet according to a first embodiment of the present invention. The lid laminate sheet 10 shown in Fig. 1 is used as a lid in a food packaging container having a container body with an opening and a lid that covers the opening. That is, the lid laminate sheet 10 is a lid material that is used as a lid by itself or a portion cut out from it is used as a lid.
[0031] The lid laminate sheet 10 includes a heat seal layer 1, a support layer 2, a gas barrier layer 3, a paper base material 4, a printed layer 5, and a functional layer (water-resistant layer) 6 having water resistance, in this order. Each layer contained in the lid laminate sheet 10 will be described below.
[0032] (Water-resistant functional layer) The water-resistant functional layer (hereinafter also referred to simply as "functional layer") 6 is a layer that, in a packaged food described below, prevents liquids outside the container, such as moisture due to condensation or oil, from penetrating into the lid and prevents the liquids from reaching layers such as the printed layer 5, the paper base material 4, and the gas barrier layer 3. By preventing liquids outside the container from reaching layers such as the printed layer 5, the paper base material 4, and the gas barrier layer 3, the functional layer 6 prevents, for example, deterioration, destruction, or reduced adhesion of these layers.
[0033] According to one example, the functional layer 6 is formed on the printing layer 5 to control the water absorbency of the partial laminate sheet, which is the portion of the lid laminate sheet 10 from the functional layer 6 to the gas barrier layer 3. The functional layer 6 controls the water absorbency of the lid laminate sheet by the Cobb method described below to 20 g / m 2 It is preferable that the material has the following water resistance.
[0034] The water absorbency here is the water absorbency obtained in the method specified in JIS P8140:1998 "Paper and paperboard - Water absorbency test method - Cobb method" when the measurement surface is the surface of the functional layer 6 and the contact time between the test piece and water is 300 seconds. This water absorbency is 20 g / m 2 It is preferable that the thickness is less than 10 g / m 2 More preferably, it is 5 g / m or less. 2 The lower limit of the water absorbency is ideally 0 g / m 2 According to one example, this water absorption is 1 g / m 2 That's all.
[0035] The functional layer 6 is preferably an overprint varnish layer (hereinafter referred to as "OP varnish layer"). According to an example, the functional layer 6 contains a water-resistant resin. As the water-resistant resin, any resin capable of realizing the above-mentioned water absorbency can be used without limitation. As the water-resistant resin, for example, polyolefin resins such as polyethylene, polypropylene, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, and vinyl chloride-vinyl acetate copolymers, silicone resins, acrylic resins, epoxy resins, polyester resins, cellulose resins, nitrocellulose resins, or urethane resins can be used. The functional layer 6 can be obtained, for example, by applying a paint containing a water-resistant resin to the paper substrate 4 on which the printing layer 5 is formed, by a known method. In addition to the water-resistant resin, the paint can further contain additives such as pigments, dyes, hardeners, leveling agents, antiblocking agents, and lubricants, and solvents.
[0036] The functional layer 6 preferably has high abrasion resistance and blocking resistance in addition to water resistance. From this viewpoint, the functional layer 6 preferably contains wax. Examples of wax contained in the functional layer 6 include polyolefin-based granular waxes mainly composed of polyethylene, polypropylene, etc., their oxides, modified derivatives with carboxyl groups, paraffin wax, microcrystalline wax, and carnauba wax dispersed in water, or self-emulsifying or emulsion-type waxes forcibly emulsified by an emulsifier. Among them, granular waxes of polyethylene wax or polypropylene wax are preferred because of their excellent effect of improving the abrasion resistance of the functional layer 6. Inorganic compounds such as metal oxide particles such as silica and titanium oxide may also be used.
[0037] When the functional layer 6 contains wax, the mass ratio of the above-mentioned water-resistant resin to the wax (water-resistant resin / wax) is, for example, 99.5 / 0.5 to 60 / 40, and for another example, 99 / 1 to 50 / 50.
[0038] The functional layer 6 preferably has high abrasion resistance and scratch resistance so as to maintain sufficient water resistance. From this viewpoint, the thickness of the functional layer 6 and the coating amount of the paint which is its material are preferably larger than the thickness of a normal OP varnish layer and the coating amount of a normal OP varnish. Here, the "coating amount" refers to the solid mass per area.
[0039] For example, in the lid laminate sheet 10 shown in FIG. 1, the coating amount of the paint for forming the functional layer 6 is 0.2 g / m 2 It is preferable to coat the film so that the coating amount is 2.0 g / m or more. 2 It is more preferable to coat the coating material so that the coating amount is, for example, 10 g / m or more. 2 The functional layer 6 is coated so as to have a thickness as described below. The thickness of the functional layer 6 is preferably 0.2 μm or more, and more preferably 2.0 μm or more. The thickness of the functional layer 6 is, for example, 10 μm or less. The functional layer 6 may be provided on the printing layer 5 by lamination.
[0040] (Printing layer) The printed layer 5 is a layer formed for putting the lid laminate sheet 10 or the lid into practical use as a commercial product. The printed layer 5 is a layer formed of ink in which additives such as various pigments, extender pigments, plasticizers, desiccants, and stabilizers are added to ink binder resins that have been used conventionally, such as urethane-based, acrylic-based, nitrocellulose-based, rubber-based, and vinyl chloride-based inks, and displays patterns such as letters and designs. The printed layer 5 can be formed by known printing methods such as offset printing, gravure printing, and silk screen printing, or known coating methods such as roll coating, knife edge coating, and gravure coating.
[0041] The thickness of the printing layer 5 is not particularly limited, and according to one example, it is in the range of 0.1 μm to 5 μm, and according to another example, it is in the range of 0.2 μm to 1 μm.
[0042] (Paper base material) The lid laminate sheet 10 includes a paper base material 4. The mass of the paper base material 4 is greater than the mass of any other layer included in the lid laminate sheet 10. The proportion of the mass of the paper base material 4 in the mass of the lid laminate sheet 10 is preferably 40% or more, more preferably 45% or more, even more preferably 50% or more, and even more preferably more than 50%. In one example, this proportion is 80% or less, in another example, 70% or less, and in yet another example, 65% or less.
[0043] When the layers other than the paper base material 4 contained in the lid laminate sheet 10 are classified into layers made of plastic and other layers, it is preferable that the mass of the paper base material 4 is larger than the total mass of the layers made of plastic and the total mass of the other layers. In this case, in Japan, the lid laminate sheet 10 can be treated as paper under the Container and Packaging Recycling Law.
[0044] Here, the above classification is in accordance with the "Container and Packaging Recycling Law Explanation Material." In other words, "plastic" is a material that contains a polymer as an essential component and is shaped and manufactured by utilizing fluidity during processing. Paints and adhesives are not included in plastics because they are unrelated to the concept of "shaping." Therefore, in the example shown in FIG. 1, the support layer 2 is a "layer made of plastic." Also, in the example shown in FIG. 1, the heat seal layer 1 when formed from heat seal varnish, the printing layer 5 formed from ink, and the functional layer 6 formed by coating are "other layers." Furthermore, when the lid laminate sheet 10 has an adhesive layer not shown, the adhesive layer is "other layers."
[0045] On the other hand, the gas barrier layer 3 is classified according to the following cases. That is, in the example shown in FIG. 1, if the gas barrier layer 3 is a layer formed on the paper base material 4 by coating or vapor deposition, it can be treated as a "paper base material" according to the above-mentioned explanatory materials, but here it is treated as an "other layer". For example, if the paper base material 4 is a barrier paper with the gas barrier layer 3 on one side thereof by coating or vapor deposition, the gas barrier layer 3 is "other layer". Also, if the gas barrier layer 3 is a layer formed on the support layer 2 by coating or vapor deposition, it is treated as an "other layer" here. Also, if the gas barrier layer 3 is at least a polymer film produced by melt molding such as extrusion processing, it is a "layer made of plastic".
[0046] The basis weight of the paper substrate 4, i.e. the mass per area, is, according to one example, between 20 and 500 g / m 2 and in another example, 40 to 100 g / m 2 If the basis weight of the paper base material 4 is increased, the lid becomes hard and the ease of opening the lid tends to decrease. If the basis weight is decreased, the strength of the lid decreases.
[0047] In addition, when the basis weight of the paper base material 4 is increased, the proportion of the mass of the paper base material 4 in the mass of the lid laminate sheet 10 also increases. However, when the basis weight of the paper base material 4 is increased, the amount of carbon dioxide emissions associated with the manufacture of the paper base material 4 and the disposal of the lid laminate sheet 10 increases.
[0048] There are no particular limitations on the paper base material 4 as long as it is made mainly of plant-derived pulp. Examples of the paper base material 4 include coated papers such as fine paper, medium-quality paper, and lightly coated paper, one-sided glossy paper, and bleached and unbleached kraft paper (acid paper or neutral paper).
[0049] The paper base material 4 is preferably a coated paper having a coating layer on at least one side. That is, the paper base material 4 is preferably a single-sided coated paper or a double-sided coated paper. The surface of the coated paper having the coating layer is superior in smoothness to the surface of paper not having the coating layer.
[0050] When the paper base material 4 is a coated paper having a coating layer on one side, the printing layer 5 can be provided, for example, on the coating layer. In this case, excellent adhesion between the paper base material 4 and the printing layer 5 can be achieved.
[0051] When the paper base material 4 is a coated paper having a coating layer on one side, the gas barrier layer 3 can be provided, for example, on the coating layer. This improves the adhesion of the gas barrier layer 3 to the paper base material 4. Also, the thickness of the gas barrier layer 3 required to exhibit barrier properties can be reduced.
[0052] When coated paper having coating layers on both sides is used as the paper base 4, excellent adhesion can be achieved between the paper base 4 and the printing layer 5. In addition, it becomes easier to achieve excellent adhesion between the paper base 4 and the gas barrier layer 3.
[0053] The coating layer contains a resin. Examples of the resin contained in the coating layer include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-α-olefin copolymers polymerized using a metallocene catalyst (single-site catalyst), polypropylene, ethylene-vinyl acetate copolymers, ionomer resins, ethylene-ethyl acrylate copolymers, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, ethylene-propylene copolymers, methylpentene polymers, acid-modified polyolefin resins obtained by modifying polyolefin resins such as polyethylene and polypropylene with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic anhydride, and fumaric acid, polyethylene terephthalate resins, polybutylene terephthalate resins, nylon resins, and thermoplastic resins such as styrene-butadiene rubber. Two or more of these resins may be used in combination, or two or more may be copolymerized. The coating layer may further contain additives, such as fillers such as silica, clay, kaolin, calcium carbonate, talc, mica, and titanium oxide.
[0054] The thickness of the coating layer is preferably in the range of 0.5 to 50 μm, and more preferably in the range of 1 to 15 μm.
[0055] (Gas barrier layer) The gas barrier layer 3 has gas barrier properties such as oxygen barrier property and water vapor barrier property. In a packaged food described below, the gas barrier layer 3 prevents gases such as oxygen, water vapor, and aroma components from outside the container from penetrating into the container. As a result, the gas barrier layer 3 prevents deterioration of the food content in the packaged food. The gas barrier layer 3 also prevents odor components and the like from the content in the packaged food from diffusing to the outside of the container. According to one example, the gas barrier layer 3 has an oxygen transmission rate of 0.1 to 100 cc / m in an atmosphere at a temperature of 30°C and a relative humidity of 70%. 2 / day / atm.
[0056] The gas barrier layer 3 is, for example, a metal layer, an inorganic oxide layer, a resin-containing layer, or a combination of two or more thereof. When microwave heating using a microwave oven is assumed, the gas barrier layer 3 is preferably an inorganic oxide layer, a resin-containing layer, or a combination thereof.
[0057] The gas barrier layer 3 may be formed by coating, by melt molding, or by vapor deposition of an inorganic oxide. Alternatively, the gas barrier layer 3 may be a metal foil such as an aluminum foil, or may be vapor deposited with a metal such as aluminum.
[0058] As the inorganic oxide, for example, silicon oxide, boron oxide, or metal oxides such as aluminum oxide, magnesium oxide, calcium oxide, potassium oxide, tin oxide, sodium oxide, titanium oxide, lead oxide, zirconium oxide, and yttrium oxide can be used.
[0059] The resin-containing layer can be formed, for example, by coating. In this case, a coating liquid containing a resin such as polyvinyl alcohol (PVA), ethylene-vinyl alcohol copolymer, ethylene-vinyl acetate copolymer, polyvinylidene chloride, polyacrylonitrile, and epoxy resin can be used. Additives such as organic or inorganic particles, layered compounds, and curing agents may be added to this coating liquid. As a coating means, various coating methods such as gravure coating, die coating, blade coating, knife coating, and bar coating can be used.
[0060] When the resin-containing layer is formed by melt molding, for example, extrusion molding techniques such as T-die and inflation can be used. In melt molding, for example, the above-mentioned resin or a mixture of the above-mentioned resin and additives is heated and melted, and the gas barrier layer 3 is processed into a film or sheet by T-die or inflation. This film or sheet is laminated to the paper substrate 4. Examples of lamination methods include a dry lamination method using a solvent-based adhesive, a non-solvent lamination method using a solvent-free adhesive, and a sand lamination method using a molten resin as an adhesive. It can also be formed directly on the paper substrate by extrusion lamination, and in this case, an adhesive layer may be formed on the paper substrate as necessary.
[0061] The gas barrier layer 3 may be formed on one surface of the support layer 2, thereby being interposed between the paper base material 4 and the support layer 2. Alternatively, the gas barrier layer 3 may be interposed between the paper base material 4 and the support layer 2 of the lid laminate sheet 10, by using a barrier paper made of a paper base material 4 having a gas barrier layer 3 on one surface. The paper base material 4 constituting the barrier paper may be a coated paper having a coating layer on at least one surface. When the paper base material 4 constituting the barrier paper has a coating layer on only one surface, the gas barrier layer 3 may be provided on the coating layer, or may be provided on the surface of the paper base material 4 on which no coating layer is formed.
[0062] The thickness of the gas barrier layer 3 is, for example, in the range of 0.01 to 30 μm, and for another example, in the range of 0.1 to 12 μm.
[0063] (Support layer) The support layer 2 improves the strength of the lid laminate sheet 10 . The support layer 2 includes polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyamide, ethylene-vinyl alcohol copolymer, polyacrylonitrile (PAN), polymethylpentene (PMP), polyvinyl alcohol resin, olefin resin, or unsaturated polyester resin. The support layer 2 may have a single-layer structure or a multi-layer structure.
[0064] The support layer 2 may be a non-stretched film or a stretched film such as a biaxially stretched film. In the case of a stretched film, it is preferable to use a biaxially stretched film. This is because the biaxial stretching reduces the variation in various physical properties such as breaking strength in the in-plane direction of the film compared to uniaxial stretching.
[0065] The support layer 2 may further contain additives such as a curing agent, a filler, an antiblocking agent, and an antistatic agent. In addition, as a material for the support layer 2, a material that is cured by irradiation with active energy rays such as ultraviolet rays and electron beams may also be used.
[0066] The thickness of the support layer 2 is preferably in the range of 3 to 60 μm, and more preferably in the range of 10 to 30 μm. If the support layer 2 is too thick, it becomes difficult to increase the proportion of the mass of the paper base material 4 in the mass of the lid laminate sheet 10.
[0067] The support layer can be formed by laminating the paper substrate via an adhesive, such as a dry lamination method using a solvent-based adhesive, a non-solvent lamination method using a solventless adhesive, or a sand lamination method using a molten resin as an adhesive. In addition, the support layer can be formed directly on the paper substrate by extruding the molten composition of the support layer, such as an extrusion lamination method, and in this case, an adhesive layer may be formed on the paper substrate if necessary.
[0068] (Heat seal layer) The heat seal layer 1 enables a lid 21 to be heat sealed to a container body 22 of a food packaging container 20 shown in FIG. 2 which will be described later.
[0069] According to one example, the heat seal layer 1 can be provided by laminating it on the support layer 2. In this case, the heat seal layer 1 is made of, for example, an easy peel sealant. Means for attaching the heat seal layer to the support layer by lamination or the like include a dry lamination method using a solvent-based adhesive, a non-solvent lamination method using a solvent-free adhesive, and a sand lamination method using a molten resin as an adhesive. In addition, when the heat seal layer is extruded with a molten resin, an extrusion lamination method can also be used.
[0070] According to another example, the heat seal layer 1 can also be formed on the support layer 2 by coating. In this case, the heat seal layer 1 is made of, for example, heat seal varnish. When the heat seal layer 1 is made of heat seal varnish, a thinner heat seal layer is more likely to be obtained than when the heat seal layer 1 is made of an easy peel sealant. This is because the easy peel sealant has a multi-layer structure. When the heat seal layer 1 is thin, it is easier to reduce the amount of petroleum-derived compounds used, so the burden on the environment can be reduced. In addition, when the heat seal layer 1 made of heat seal varnish is used, it is possible to reduce costs compared to when the heat seal layer 1 made of an easy peel sealant is used. As a coating means, various coating methods such as gravure coating, die coating, blade coating, knife coating, and bar coating can be used.
[0071] The heat seal layer 1 contains an ethylene-vinyl acetate copolymer and a fatty acid amide additive. The heat seal layer 1 has a peak adhesive strength measured by a probe tack test in the range of -28 gf to 0 gf.
[0072] The peak strength of the adhesive force of the heat seal layer 1 in the probe tack test indicates the maximum resistance (adhesive force) when a probe is pressed against the main surface of the heat seal layer 1 of the lid laminate sheet 10 under the conditions described below and then pulled up. Note that the peak strength is a measured value, so it is a negative value. The larger the absolute value of the peak strength, the stronger the adhesive force, and the smaller the absolute value of the peak strength, the weaker the adhesive force.
[0073] As described above, it was particularly difficult to achieve both blocking resistance and heat sealability when the heat seal layer 1 was made of a sealant varnish. It was found that when the heat seal layer 1 contained an ethylene-vinyl acetate copolymer and a fatty acid amide additive, and the peak strength of the adhesive force measured by a probe tack test in the heat seal layer 1 was within the range of -28 gf to 0 gf, a lid having both blocking resistance and heat sealability could be realized regardless of whether the heat seal layer 1 was made of a sealant film or a sealant varnish. The mechanism that enabled both blocking resistance and heat sealability to be achieved will be described below using the example of the heat seal layer 1 being a layer derived from a heat seal varnish.
[0074] The heat seal varnish used to form the heat seal layer 1 is an aqueous dispersion containing an ethylene-vinyl acetate copolymer (hereinafter also referred to as "EVA copolymer" (Ethylene-vinyl acetate); EVA) and a fatty acid amide additive. In the aqueous dispersion heat seal varnish, the EVA copolymer and the fatty acid amide additive are in a partially compatible state. When this is formed into a heat seal layer, the fatty acid amide additive bleeds out to the surface side of the heat seal layer 1 opposite the support layer 2. Therefore, when the heat seal layer 1 is viewed in the thickness direction, the concentration of the fatty acid amide additive is high on and near the surface.
[0075] The blocking resistance of the lid laminate sheet 10 is improved by the bleeding out phenomenon of the fatty acid amide additive to the EVA copolymer in the heat seal layer 1. That is, when the lid laminate sheet 10 is stored in a rolled state, the bleeding out phenomenon of the fatty acid amide additive reduces the contact area between the heat seal layer 1 and the functional layer 6 overlapping this layer, improving the blocking resistance.
[0076] Meanwhile, the compatibility between the EVA copolymer and the fatty acid amide additive in the heat seal layer 1 changes depending on the temperature environment. When the heat seal layer 1 is heated to a temperature above the melting point during heat sealing, the compatibility between the EVA copolymer and the fatty acid amide additive increases. This increase in compatibility causes the fatty acid amide additive that has bled onto the surface of the heat seal layer 1 to become compatible with the EVA copolymer again and become uniformly distributed in the thickness direction. As a result, the fatty acid amide additive that was unevenly distributed on the surface and near the surface of the heat seal layer 1 is reduced, improving the seal strength. In the following, the phenomenon in which the fatty acid amide additive that has bled onto the surface of the heat seal layer 1 becomes compatible with the EVA copolymer again and becomes uniformly distributed in the thickness direction due to heating is referred to as "redissolution of the fatty acid amide additive".
[0077] The present inventors have confirmed this phenomenon from an infrared absorption spectrum (ATR-FTIR spectrum) obtained by Fourier transform infrared spectroscopy (ATR-FTIR analysis) using an attenuated total reflection method (ATR method) on the surface of the heat seal layer 1 opposite to the support layer 2 (ATR: Attenuated Total Reflection, FTIR: Fourier Transform Infrared Spectroscopy). That is, it has been confirmed that a peak characteristic of a fatty acid amide-based additive disappears when the heat seal layer 1 is heated to a temperature above the melting point, and then this peak reappears when the heat seal layer 1 is returned to room temperature after a certain period of time.
[0078] The present inventors have found that when the peak adhesive strength of the heat seal layer 1 measured by a probe tack test is within the range of -28 gf to 0 gf, both blocking resistance and heat sealability due to the above phenomenon are achieved. That is, blocking is suppressed by the bleeding-out phenomenon of the fatty acid amide additive in the EVA copolymer, and the heat seal strength is improved by the re-dissolution of the fatty acid amide additive in the EVA copolymer.
[0079] The peak strength of the adhesive force of the heat seal layer 1 measured by a probe tack test is preferably within the range of -25 gf to -5 gf, and more preferably within the range of -23 gf to -10 gf.
[0080] Here, the peak strength of the adhesive force measured by the probe tack test can be controlled, for example, by the selection of the fatty acid amide-based additive, the blending mass ratio of the fatty acid amide-based additive to the EVA-based copolymer, or the saturation solubility of the fatty acid amide-based additive in the EVA-based copolymer.
[0081] Ethylene-vinyl acetate copolymer An ethylene-vinyl acetate copolymer (EVA copolymer) is a copolymer containing at least an ethylene-based structural unit derived from an ethylene monomer and a vinyl acetate-based structural unit derived from a vinyl acetate monomer. The EVA copolymer may contain a structural unit derived from a third monomer in addition to the ethylene-based structural unit and the vinyl acetate-based structural unit.
[0082] Since the EVA-based copolymer has heat-sealing suitability, it is suitable for use as the main component of the heat-sealing layer 1. In addition, the EVA-based copolymer has the characteristics of low hydrophilicity and relatively high oil resistance. This characteristic is considered to be one of the factors that cause the above-mentioned phenomenon of bleeding out and re-dissolution of the fatty acid amide-based additive. In addition, the EVA-based copolymer has excellent cold resistance, chemical resistance, and other properties, and has relatively high stability of physical properties, making it suitable for use as a material for packaging containers that contain chilled and frozen foods. Furthermore, when the heat-sealing layer 1 is a layer derived from a heat-sealing varnish, the EVA-based copolymer is used as an aqueous dispersion as described above, so the environmental load is also small.
[0083] The content of ethylene-based structural units in the EVA-based copolymer may be, for example, in the range of 60% by mass to 96% by mass, and the content of vinyl acetate-based structural units in the EVA-based copolymer may be, for example, in the range of 4% by mass to 40% by mass.
[0084] The glass transition temperature (Tg) of the EVA copolymer is preferably -45°C or higher, more preferably -40°C or higher. If the glass transition temperature of the EVA copolymer is low, the tackiness at room temperature increases, so from the viewpoint of blocking resistance, it is preferable that the glass transition temperature is not too low. The upper limit of the glass transition temperature is not particularly limited, but may be, for example, -10°C or lower.
[0085] The glass transition temperature of the EVA copolymer can be adjusted, for example, by the content of the constituent units constituting the copolymer. In general, the glass transition temperature of the copolymer decreases as the content of the ethylene-based constituent units increases, and the glass transition temperature of the copolymer increases as the content of the vinyl acetate-based constituent units increases. Here, the glass transition temperature means a temperature measured in accordance with JISK7121:2012. Specifically, it is a temperature measured by DSC (differential scanning calorimeter) in accordance with 8.6(3) after heat treatment in accordance with JISK7121:2012, 3(3). The heat seal layer 1 may contain two or more EVA copolymers having different glass transition temperatures.
[0086] The melting point (Tm) of the EVA-based copolymer means a temperature measured by the same measuring method as the glass transition temperature. Specifically, it is a temperature measured by DSC (differential scanning calorimeter) according to 8.6(1) after heat treatment according to 3(2) of JIS K7121:2012. The melting point of the EVA-based copolymer is preferably in the range of 40 to 120°C, more preferably in the range of 45 to 100°C. If the melting point of the EVA-based copolymer is too low, the storage property is reduced. Specifically, during storage at room temperature, the heat seal layer 1 is likely to melt and deform, and the blocking resistance is likely to decrease due to the melting of the heat seal layer 1. Also, during storage at room temperature, the state in which the fatty acid amide-based additive bleeds out is likely to become unstable. On the other hand, if the melting point of the EVA-based copolymer is too high, the heat seal property is likely to decrease. Specifically, the melt viscosity increases relative to the temperature during heat sealing, reducing the ability to conform to the adherend, and the compatibility with the fatty acid amide additive decreases, reducing the resolubility of the fatty acid amide additive, which reduces the heat sealability. Also, when the EVA copolymer is used as an aqueous dispersion of emulsion such as heat seal varnish, if the melting point of the EVA copolymer is too high, the emulsion will not fuse well and the film-forming ability will tend to decrease.
[0087] The mass average molecular weight of the EVA copolymer is not particularly limited, and can be adjusted to be within the range of, for example, tens of thousands to millions. The lower the mass average molecular weight of the EVA copolymer, the higher the compatibility with the fatty acid amide additive and the better the resolubility of the fatty acid amide additive, which is preferable from the viewpoint of heat sealability. However, if the mass average molecular weight is too low, the mechanical properties of the heat seal layer 1 are reduced, and cracks and scratches are likely to occur. In addition, if the mass average molecular weight of the EVA copolymer is too high, the melt viscosity at the temperature during heat sealing is high, and the followability to the adherend is reduced, and stability is likely to decrease. In addition, when used as an aqueous dispersion of emulsion such as heat seal varnish, if the mass average molecular weight of the EVA copolymer is too high, the fusion of the emulsion is slow and the film formability is likely to decrease. In addition, the "mass average molecular weight" here can be obtained by converting the molecular weight measured using gel permeation chromatography (GPC) into polystyrene equivalent.
[0088] Fatty acid amide additives The fatty acid amide additive is a compound having, in the molecule, a hydrophobic portion suitable for blocking resistance and a hydrophilic portion suitable for causing the bleed-out phenomenon.
[0089] The fatty acid amide additive may be a primary amide compound, a secondary amide compound, or a tertiary amide compound. In one embodiment, the fatty acid amide additive is preferably a primary or secondary amide compound, and more preferably a secondary amide compound. The tertiary amide compound has a lower hydrophilicity at the amide site than the primary and secondary amide compounds, and is less likely to cause a bleed-out phenomenon. In addition, the primary amide compound can exert an effect similar to that of the secondary amide compound in terms of bleed-out and re-dissolution, but may cause defects such as poor appearance due to bleed-out, such as whitening, or contamination of the device or other products due to the release of the aliphatic amide additive from the heat seal layer 1.
[0090] In one embodiment, the fatty acid amide additive preferably has an unsaturated hydrocarbon group as a hydrophobic moiety. A fatty acid amide compound having an unsaturated hydrocarbon group as a hydrophobic moiety has a saturated hydrocarbon group as a hydrophobic moiety, and the steric hindrance of the hydrophobic moiety is higher than that of a fatty acid amide compound having no unsaturated hydrocarbon group. This makes it difficult for the additives to aggregate (associate) with each other, and bleed-out is more likely to occur. In addition, many fatty acid amide compounds having no unsaturated hydrocarbon group as a hydrophobic moiety have a melting point of more than 100°C, and in this case, the resolubility of the fatty acid amide additive during heat sealing is low, so that the heat sealability tends to decrease.
[0091] The fatty acid amide-based additive may be a monoamide compound or a bisamide compound. In one embodiment, the fatty acid amide-based additive is preferably a monoamide compound.
[0092] Examples of fatty acid amide additives that satisfy the above-mentioned preferred conditions include fatty acid primary monoamides having an unsaturated hydrocarbon group as a hydrophobic moiety. In this case, the number of carbon atoms contained in the unsaturated hydrocarbon group is preferably, for example, 16 to 40. Specific examples of such fatty acid amide additives include N-oleyl palmitamide, N-stearyl erucamide, and erucic acid amide.
[0093] The molecular weight of the fatty acid amide additive is preferably within the range of 200-1,000.
[0094] The melting point of the fatty acid amide additive is preferably in the range of 40 to 120° C., more preferably in the range of 50 to 100° C. If the melting point of the fatty acid amide additive is too low, the bleed-out fatty acid amide additive may re-dissolve in the EVA copolymer during storage at room temperature, which may reduce the blocking resistance. Also, if the melting point of the fatty acid amide additive is too high, the re-solubility of the fatty acid amide additive during heat sealing is reduced, which may reduce the heat sealability.
[0095] The saturation solubility of the fatty acid amide additive in the EVA copolymer is preferably in the range of 0.01 mass ppm to 0.1 mass ppm. If the saturation solubility of the fatty acid amide additive in the EVA copolymer is too low, it becomes difficult to adjust the amount of the fatty acid amide additive that bleeds out. If the saturation solubility of the fatty acid amide additive is too high, the amount of the fatty acid amide additive added becomes too large, which tends to inhibit the function of the heat seal layer 1.
[0096] In the heat seal layer 1, the mixing ratio of the fatty acid amide additive to the EVA copolymer is such that the amount of the fatty acid amide additive added is equal to or greater than the saturated solubility described above. According to one example, the mass ratio of the fatty acid amide additive to the EVA copolymer is preferably 0.1% by mass or more, more preferably 0.2% by mass or more. If the mixing ratio of the fatty acid amide additive to the EVA copolymer is too low and is less than the saturated solubility described above, the fatty acid amide additive does not bleed out when the film is formed. In addition, the mass ratio of the fatty acid amide additive to the EVA copolymer is preferably 0.9% by mass or less, more preferably 0.8% by mass or less. If the mixing ratio of the fatty acid amide additive to the EVA copolymer is too high, poor appearance such as whitening due to bleed out, or problems such as contamination of the device or other products due to the release of the fatty acid amide additive from the heat seal layer 1 may occur.
[0097] The heat seal layer 1 may contain other components such as other resins, such as polyolefins, and additives, within the range that does not impair the above-mentioned effects obtained by containing the EVA copolymer and the fatty acid amide additive.
[0098] ·particle The heat seal layer 1 may further contain particles. It is preferable that the particles function as a lubricant. The lubricant is added to the heat seal layer to roughen the surface and reduce the contact area with the layer that comes into contact during winding of the film, thereby imparting slipperiness. Poor slipperiness may cause problems such as poor winding of the film, inclusion of wrinkles, and difficulty in uniform winding. Although it is possible to obtain the desired slipperiness by using a fatty acid amide-based additive, if the slipperiness is to be further improved by using only a fatty acid amide-based additive, the amount of the additive may be excessive. If an excessive amount of the fatty acid amide-based additive is added, a part of the additive may be liberated from the heat seal layer 1. If the additive is liberated, problems such as contamination of the device or other products, migration of the contents to the contents, etc. may occur.
[0099] The above-mentioned particles may be inorganic particles or organic particles, and one or more kinds may be used. Examples of inorganic particles include spherical silica, amorphous silica, clay, kaolin, calcium carbonate, talc, and mica, and examples of metal oxides include boron oxide, aluminum oxide, magnesium oxide, calcium oxide, potassium oxide, tin oxide, sodium oxide, titanium oxide, lead oxide, zirconium oxide, and yttrium oxide. Examples of organic particles include polymers of (meth)acrylate monomers or (meth)acrylate oligomers, and polyolefins such as polyethylene and polypropylene.
[0100] The average particle diameter of the particles is preferably 40 μm or less. If the average particle diameter is large, the amount of particles that penetrate the functional layer 6 that contacts the heat seal layer 1 during winding increases, and blocking resistance is likely to decrease. The average particle diameter of the particles is more preferably within the range of 5 to 40 μm. Here, the average particle diameter of the particles is the median diameter of the volume-based particle size distribution measured using a laser diffraction particle size distribution measuring device (e.g., Shimadzu SALD-7100h).
[0101] Although the above particles can contribute to improving blocking resistance, the desired blocking resistance cannot be obtained by using only the above particles without using fatty acid amide additives. That is, in order to obtain the desired blocking resistance by using only the above particles, a certain amount of addition is required. In that case, the particles penetrate into the layer in contact with the heat seal layer when the lid laminate sheet is wound up, which leads to a decrease in blocking resistance, and the desired blocking resistance cannot be obtained. This tendency is particularly noticeable when the HS layer is a cured film of a coating film made of HS varnish.
[0102] When the heat seal layer 1 contains the above particles, the content of the above particles in the heat seal layer 1 is 11% by mass or less with respect to the total mass of the heat seal layer 1. When the content of the above particles exceeds 11% by mass, the phenomenon that the particles are pierced into the layer in contact with the heat seal layer when the above-mentioned lid laminate sheet is wound up tends to occur, and blocking resistance decreases. In addition, since the above particles do not have sealing properties, it may also lead to a decrease in heat seal strength. These tendencies are particularly noticeable when the heat seal layer is a cured film of a coating film made of heat seal varnish. When the heat seal layer 1 contains the above particles, the content of the above particles in the heat seal layer 1 is more preferably 10% by mass or less with respect to the total mass of the heat seal layer 1.
[0103] The thickness of the heat seal layer 1 is preferably in the range of 2.0 to 6.0 μm, more preferably in the range of 2.5 to 5.5 μm. If the thickness of the heat seal layer 1 is less than 2.0 μm, the amount of bleed-out of the fatty acid amide-based additive decreases with the decrease in the volume of the heat seal layer 1, making it difficult to obtain the desired blocking resistance. If the thickness of the heat seal layer 1 is too thin, the heat sealability is likely to decrease regardless of the presence or absence of bleed-out of the fatty acid amide-based additive. If the heat seal layer 1 is too thick, it takes a long time to dry, so the productivity is likely to decrease. It is also not preferable from the viewpoint of environmental load.
[0104] (Adhesive layer) The lid laminate sheet 10 may further include one or more adhesive layers. According to one example, the lid laminate sheet 10 may include an adhesive layer between the support layer 2 and the gas barrier layer 3 to bond them. According to another example, the lid laminate sheet 10 may include an adhesive layer between the gas barrier layer 3 and the paper base material 4 to bond them. According to another example, the lid laminate sheet 10 may include an adhesive layer between the heat seal layer 1 and the support layer 2 to bond them. According to another example, the lid laminate sheet 10 may include two or more of the above-mentioned adhesive layers.
[0105] The adhesive layer is made of an adhesive resin or adhesive that can provide the required adhesive strength depending on the material of the layer to be bonded thereto.
[0106] The adhesive resin may be one or more resins selected from polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, and copolymers of ethylene and α-olefin polymerized using a metallocene catalyst; ethylene-unsaturated carboxylic acid copolymers such as ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-ethyl acrylate copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylate copolymer, and ethylene-maleic acid copolymer; and ionomer resins.
[0107] The adhesive is, for example, an adhesive composition obtained by mixing a first composition containing a base agent and a solvent with a second composition containing a curing agent and a solvent. The adhesive layer obtained from this adhesive contains a cured product produced by the reaction of the base agent and the curing agent in the adhesive composition.
[0108] An example of the base agent is polyol. An example of the curing agent is isocyanate compound. An example of the adhesive is an ether-based two-liquid reactive adhesive or an ester-based two-liquid reactive adhesive.
[0109] The cured product of the ether-based two-liquid reactive adhesive is, for example, polyether polyurethane, which is produced by reacting a polyether polyol as a base agent with an isocyanate compound as a curing agent.
[0110] Examples of the cured product of the ester-based two-component reactive adhesive include polyester polyurethane and polyester. The polyester polyurethane is produced by reacting a polyester polyol as a base material with an isocyanate compound as a curing agent.
[0111] In the two-component reactive adhesive, an acrylic polyol may be used as a base agent. The adhesive composition may not contain a solvent as long as it melts or has a low viscosity when heated.
[0112] The thickness of the lid laminate sheet 10 is, for example, preferably in the range of 40 to 170 μm, and more preferably in the range of 45 to 160 μm.
[0113] According to one example, the lid laminate sheet 10 has a mass per area of 45 to 160 g / m 2 and preferably in the range of 50 to 150 g / m 2 It is more preferable that the value is within the range of 100%. If this value is reduced, the strength of the lid body tends to decrease. If this value is increased, the lid body tends to become hard and the ease of opening tends to decrease. In addition, if this value is increased, the cost increases and the amount of carbon dioxide emitted during production and exhaust increases.
[0114] [Second embodiment] The lid body according to the second embodiment of the present invention is a lid body obtained from the lid body laminate sheet according to the first embodiment described above. An example of the lid body according to the second embodiment is the lid body 21 described later with reference to Fig. 2. As described in relation to the lid body laminate sheet 10, the lid body according to this embodiment is a lid body having a high mass ratio of the paper base material, and has both good blocking resistance and heat sealability.
[0115] [Third embodiment] Fig. 2 is a cross-sectional view showing a food packaging container according to a third embodiment of the present invention. The food packaging container 20 shown in Fig. 2 includes a container body 22 having an opening, and a lid 21 that covers the opening.
[0116] The container body 22 is, for example, a cylindrical shape with a bottom. Here, the container body 22 includes a bottom, a body (or a side wall), and a flange 22a. The flange 22a expands outward at the position of the upper opening of the body.
[0117] The container body 22 includes, for example, an olefin resin such as polypropylene (PP). The container body 22 may further include a component such as ethylene-vinyl alcohol copolymer (EVOH) in order to enhance its gas barrier properties. The container body 22 may further include an additive, for example, an additive for improving processability, designability, and chemical durability.
[0118] The container body 22 may have a single-layer structure or a multi-layer structure. This multi-layer structure may be a two-layer structure or may include three or more layers. In the latter case, the multi-layer structure may be a three-layer structure (PP / PP+EVOH / PP) including a gas barrier layer, for example, a layer containing a component such as the above-mentioned ethylene-vinyl alcohol copolymer, as an intermediate layer.
[0119] The container body 22 may be made of paper. When the contents include a liquid, the container body 22 may have a multi-layer structure including a paper base material and a layer of resin or the like provided on the surface of the container body 22 facing the contents to prevent the liquid from seeping into the paper base material. The container body 22 may be made of paper leaves, paper powder, pulp, or recycled paper. The container body 22 may be formed by folding or pasting a sheet including paper leaves, as in the manufacture of paper packs, press molding of a sheet using a mold, or other general-purpose techniques such as pulp molding. By using paper for the container body 22, it is possible to reduce the amount of carbon dioxide emissions associated with the manufacture and disposal of the food packaging container 20 as a whole, and therefore the burden on the environment is reduced.
[0120] The lid body 21 is the lid body laminate sheet 10 or a cut-out thereof. After the contents are placed in the container body 22, the lid body 21 is heat-sealed to the flange 22a via the heat seal layer 1. In this heat sealing, the sealing temperature, sealing pressure, and sealing time can be appropriately set.
[0121] [Fourth embodiment] The packaged food according to the fourth embodiment of the present invention is obtained by packaging food in the food packaging container according to the third embodiment described above. The food to be packaged is not particularly limited, but is preferably a chilled food or a frozen food. The chilled food and frozen food are, for example, cooked or processed foods. The chilled food and frozen food are, for example, grilled fish, boiled fish, or side dishes.
[0122] In this packaged food, as described above, the heat seal strength between the lid 21 and the container body 22 is preferably smaller than the breaking strength of the support layer 2 included in the lid 21. This heat seal strength is preferably in the range of 5N / 15mm to 60N / 15mm, more preferably in the range of 10N / 15mm to 50N / 15mm. The difference between the breaking strength of the support layer 2 and the heat seal strength between the lid 21 and the container body 22 is preferably in the range of 5 to 60N / 15mm, more preferably in the range of 10 to 40N / 15mm. Here, the heat seal strength is a value obtained by a method specified in JIS Z0238:1998 "Test method for heat-sealed flexible packaging bags and semi-rigid containers".
[0123] In the manufacture of this packaged food, before the lid 21 is heat-sealed to the container body 22, for example, after the contents are placed in the container body 22 and before the lid 21 is heat-sealed to the container body 22, the gas in the container body 22 may be replaced by a known method. For example, the container body 22 may be filled with an inert gas. By appropriately changing the gas composition in the container, it is possible to suppress the growth of bacteria and extend the quality retention period, to prevent oxidation and thereby to maintain the flavor, color, etc. of the food for a long time, and to prevent the loss of vitamins. The replacement gas is appropriately selected depending on the type of food that is the content. As the replacement gas, a mixed gas of oxygen gas, nitrogen gas, and carbon dioxide gas is preferably used. EXAMPLES
[0124] Tests carried out in relation to the present invention are described below. <1> Manufacturing of laminated sheets for lids (Example 1) The lid laminate sheet 10 shown in FIG. 1 was produced by the following method. First, the paper base material 4 has a basis weight of 52.3 g / m 2 A single-sided coated paper with a mass per area of 37.3 g / m was prepared. 2The coating layer was obtained by applying a coating solution containing polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), silica and layered silicate as main components and water as the main solvent to the imitation paper. The obtained coating layer had a mass of solids per area of 15 g / m 2 It was.
[0125] Next, a multicolor gravure printer was used to successively form a printed layer 5 and a functional layer 6 on the surface of the paper base material 4 on which the coating layer was formed, thereby obtaining a laminate consisting of the paper base material 4, the printed layer 5, and the functional layer 6. The printed layer 5 was formed using a normal printing ink. The coating amount of the printing ink was 1.0 g / m 2 The functional layer 6 was formed using an OP varnish whose main components were nitrocellulose resin and polyethylene-based granular wax. The application amount of the OP varnish was 0.5 g / m 2 It was decided.
[0126] Next, a polyethylene terephthalate (PET) film with a thickness of 12 μm was prepared as the support layer 2. Alumina was vapor-deposited as an inorganic oxide film on one surface of this support layer 2 to form a gas barrier layer 3. This resulted in a gas barrier film including a support layer 2 made of a PET film and a gas barrier layer 3 made of an inorganic oxide (alumina) layer. The mass per area of this gas barrier film was 16.8 g / m 2 It was.
[0127] Next, the gas barrier film was attached to the laminate consisting of the paper base material 4, the printing layer 5, and the functional layer 6 by dry lamination. For dry lamination, a dry laminating agent was first applied to the surface of the gas barrier layer 3 of the gas barrier film using a gravure coater to form an adhesive layer (not shown). A two-part reactive adhesive containing a polyester-based base agent and an isocyanate-based curing agent was used as the dry laminating agent. The amount of dry laminating agent applied was 3.0 g / m 2 Next, the laminate and the gas barrier film were attached to each other with the adhesive layer sandwiched therebetween, so that the gas barrier layer 3 faced the paper base material 4.
[0128] Thereafter, the heat seal varnish A was applied by gravure printing onto the support layer 2 of the laminate including the support layer 2, the gas barrier layer 3, the paper base material 4, the printing layer 5, and the functional layer 6, to form the heat seal layer 1. The heat seal varnish A had a mass per area of 3 g / m in a dry state. 2 The varnish was applied to a thickness of 3 μm. Heat seal varnish A was prepared by adding N-oleyl palmitamide as a fatty acid amide additive and amorphous silica particles with an average particle size of 30 μm to an aqueous emulsion containing ethylene-vinyl acetate copolymer (EVA copolymer) as the main component. The amount of N-oleyl palmitamide added was 0.2 mass% relative to the EVA copolymer contained in the aqueous emulsion, and the amount of amorphous silica particles added was 10 mass% relative to the total solid content contained in heat seal varnish A.
[0129] The ethylene-vinyl acetate copolymer used here has a glass transition temperature (Tg) of -27°C and a melting point (Tm) in the range of 50 to 90°C. In this manner, a lid laminate sheet was obtained.
[0130] (Example 2) A laminate sheet for a lid was produced in the same manner as in Example 1, except for the following points: In this example, the amount of the irregular silica particles added was changed from 10% by mass to 6% by mass.
[0131] (Example 3) A laminate sheet for a lid was produced in the same manner as in Example 1, except for the following points: In this example, irregular silica particles were not added.
[0132] (Example 4) A lid laminate sheet was produced in the same manner as in Example 1, except for the following points: In this example, the mass per area of the heat seal layer 1 was 3 g / m 2 and 3μm thick, 5g / m 2 and 5 μm.
[0133] (Example 5) A lid laminate sheet was produced in the same manner as in Example 1, except for the following points: In this example, the amount of amorphous silica particles added was changed from 10% by mass to 6% by mass, and the mass per area of the heat seal layer 1 was 3 g / m 2 and 3μm thick, 5g / m 2 and 5 μm.
[0134] (Example 6) A lid laminate sheet was produced in the same manner as in Example 1, except for the following points: In this example, no amorphous silica particles were added, and the mass per area of the heat seal layer 1 was 3 g / m 2 and 3μm thick, 5g / m 2 and 5 μm.
[0135] (Example 7) A lid laminate sheet was produced in the same manner as in Example 1, except for the following points: In this example, the average particle size of the irregular silica particles was changed from 30 μm to 10 μm, and the amount of the irregular silica particles added was changed from 10 mass% to 6 mass%.
[0136] (Example 8) A laminate sheet for a lid was produced in the same manner as in Example 1, except for the following points: In this example, the average particle size of the irregular silica particles was changed from 30 μm to 5 μm.
[0137] (Example 9) A lid laminate sheet was produced in the same manner as in Example 1, except for the following points: In this example, the average particle size of the irregular silica particles was changed from 30 μm to 10 μm, the amount of the irregular silica particles added was changed from 10% by mass to 6% by mass, and the mass per area of the heat seal layer 1 was changed to 3 g / m 2 and 3μm thick, 5g / m 2 and 5 μm.
[0138] (Example 10) A lid laminate sheet was produced in the same manner as in Example 1, except for the following points: In this example, the average particle size of the amorphous silica particles was changed from 30 μm to 5 μm, and the mass per area of the heat seal layer 1 was changed to 3 g / m 2 and 3μm thick, 5g / m 2 and 5 μm.
[0139] Comparative Example 1 A lid laminate sheet was produced in the same manner as in Example 1, except for the following points: In this example, no fatty acid amide additive was added.
[0140] Comparative Example 2 A lid laminate sheet was produced in the same manner as in Example 1, except for the following points: In this example, no fatty acid amide additive was added, and the amount of amorphous silica particles added was changed from 10% by mass to 6% by mass.
[0141] Comparative Example 3 A laminate sheet for a lid was produced in the same manner as in Example 1, except for the following points: In this example, no fatty acid amide additive was added, and no irregular silica particles were added.
[0142] Comparative Example 4 A lid laminate sheet was produced in the same manner as in Example 1, except for the following points: In this example, no fatty acid amide additive was added, and the mass per area of the heat seal layer 1 was 3 g / m 2 and 3μm thick, 5g / m 2 and 5 μm.
[0143] Comparative Example 5 A lid laminate sheet was produced in the same manner as in Example 1, except for the following points: In this example, no fatty acid amide additive was added, the amount of amorphous silica particles added was changed from 10% by mass to 6% by mass, and the mass per area of the heat seal layer 1 was 3 g / m 2 and 3μm thick, 5g / m 2 and 5 μm.
[0144] Comparative Example 6 A lid laminate sheet was produced in the same manner as in Example 1, except for the following points: In this example, no fatty acid amide additive was added, no amorphous silica particles were added, and the mass per area of the heat seal layer 1 was 3 g / m 2 and 3μm thick, 5g / m 2 and 5 μm.
[0145] Comparative Example 7 A lid laminate sheet was produced in the same manner as in Example 1, except for the following points: In this example, the amount of amorphous silica particles added was changed from 10% by mass to 11.5% by mass, and the mass per area of the heat seal layer 1 was 3 g / m 2 and 3μm thick, 5g / m 2 and 5 μm.
[0146] <2> evaluation (mass percentage of paper, plastic and others) The layer structure of each lid laminate sheet was classified into "paper", "plastic" and "other" as explained above in accordance with the "Container and Packaging Recycling Law Explanation Material" and the mass ratio of each layer in the lid laminate sheet was calculated. In this case, the paper base material 4 is classified as "paper", the support layer 2 is classified as "plastic", and the heat seal layer 1, gas barrier layer 3, adhesive layer, printing layer 5 and functional layer 6 are classified as "other".
[0147] For each mass measurement, the mass was measured on a 200mm x 250mm area and expressed in g / m 2 The mass of the support layer 2 and the paper base material 4 was measured directly, and the mass of the others (heat seal layer 1, gas barrier layer 3, adhesive layer, printing layer 5 and functional layer 6) was calculated by subtracting the mass of the support layer 2 and the paper base material 4 from the total mass of the lid laminate sheet. The results are shown in Table 1.
[0148] (Peak adhesive strength) The heat seal layer 1 of each lid laminate sheet was measured for peak adhesive strength by a probe tack test. In the test, a probe tack device (TAC-1000, manufactured by Rhesca Co., Ltd.) was used to press a probe against the heat seal layer under the following conditions, and the maximum resistance (adhesive strength) when pulled up was measured as the peak adhesive strength. The peak strength is a measured value, so it is a negative value. The larger the absolute value of the peak strength, the greater the adhesive strength, and the smaller the absolute value of the peak strength, the weaker the adhesive strength. The number of measurements was 5 or more, and the average value is shown in Table 1 as the peak adhesive strength.
[0149] The measurement conditions are as follows. Probe: 10mm diameter cylindrical Probe material: SUS Temperature: Probe 40℃, Test bench 40℃ Pressing pressure: 0.2MPa Pressing time: 40 seconds Pulling speed: 2mm / sec
[0150] (Heat seal strength) The heat seal strength of each lid laminate sheet was measured. A three-layered polypropylene resin sheet (PP / PP+EVOH4% / PP) (B-130WE3, Idemitsu Unitech) including a pair of polypropylene (PP) layers and a layer of a mixture of polypropylene and 4% ethylene-vinyl alcohol copolymer (EVOH) was used as the adherend.
[0151] First, each lid laminate sheet and the polypropylene resin sheet were heat-sealed to obtain a test piece. The width of the test piece was 15 mm, and the length was 50 mm. Nine test pieces were prepared for each lid laminate sheet, three for each sealing temperature. The sealing temperatures were 190°C, 210°C, and 230°C, the sealing pressure was 0.2 MPa, the sealing time was 2 seconds, and the width of the seal bar was 5 mm. Heat sealing was performed using a heat seal tester (product name "TP-701-B"; manufactured by Tester Sangyo Co., Ltd.).
[0152] Next, the heat seal strength between each lid laminate sheet and the polypropylene resin sheet was measured by a method conforming to JIS Z0238:1998. Specifically, the test piece was opened 180° with the heat seal part in the center, and a tensile load was applied to peel or break the heat seal part. The distance between the chucks was 50 mm, and the relative movement speed, i.e., the peel speed, was 1000 mm / min.
[0153] The heat seal strength was measured in the MD and TD of the lid laminate sheet using a Tensilon universal testing machine. Measurements in the MD and TD were performed three times for each of the sealing temperatures of 190°C, 210°C, and 230°C, and the average of nine measured values was calculated for each of the MD and TD. The heat sealability was evaluated from the obtained average values according to the following criteria. The results are shown in Table 1.
[0154] A: MD is 11N / 15mm or more and TD is 8.5N / 15mm or more. B: MD is 10N / 15mm or more and less than 11N / 15mm, and TD is 7.5N / 15mm or more, or MD is 10N / 15mm or more and TD is 7.5N / 15mm or more and less than 8.5N / 15mm. C: MD is less than 10N / 15mm, or TD is less than 7.5N / 15mm.
[0155] (Blocking resistance test) A blocking test was performed on each lid laminate sheet according to JIS K6404-3:2015. Two square test pieces with sides of 45 mm were cut out from each lid laminate sheet, and the heat seal layer 1 and the functional layer 6 were stacked so that they faced each other to prepare a sample. This was sandwiched between a blocking tester, and a load of 200 kg was applied to an area of 45 mm x 45 mm of the sample. After storing the sample in this state for 4 days under an environment of a temperature of 40 ° C and a relative humidity of 20%, the two test pieces were peeled off, and the blocking resistance was evaluated according to the following criteria. In the following criteria, the state where there is a "transferred matter" means that a part of the functional layer or the printing layer has peeled off from the paper substrate and transferred to the heat seal layer. The results are shown in Table 1.
[0156] A: No metastases B: There is metastasis, but it is small and not noticeable. C: Metastases are prominent D: The functional layer and the heat seal layer are firmly attached to each other, and the paper is peeled off.
[0157] [Table 1]
[0158] The present invention is not limited to the above-mentioned embodiment, and can be modified in various ways without departing from the gist of the present invention. The embodiments may be combined as appropriate, and in that case, the combined effect can be obtained. Furthermore, the above-mentioned embodiment includes various inventions, and various inventions can be extracted by combinations selected from the multiple components disclosed. For example, if the problem can be solved and the effect can be obtained even if some components are deleted from all the components shown in the embodiment, the configuration from which the components are deleted can be extracted as an invention. [Explanation of symbols]
[0159] Reference Signs List 1...heat seal layer, 2...support layer, 3...gas barrier layer, 4...paper base material, 5...printed layer, 6...water-resistant functional layer, 10...laminated sheet for lid, 20...food packaging container, 21...lid, 22...container body, 22a...flange.
Claims
1. A laminated sheet for a lid used for a lid of a food packaging container having a container body with an opening and a lid covering the opening, the laminated sheet comprising, in this order, a water-resistant functional layer, a paper base material, a support layer, and a heat seal layer; The heat seal layer contains an ethylene-vinyl acetate copolymer and a fatty acid amide additive, and may further contain particles, provided that, when the particles are contained, the content of the particles in the heat seal layer is 11% by mass or less, and The heat seal layer has a peak adhesive strength in the range of -28 gf to 0 gf as measured by a probe tack test.
2. 2. The laminate sheet for a lid according to claim 1, wherein the particles have an average particle size of 40 [mu]m or less.
3. The laminate sheet for a lid body according to claim 1, wherein when layers other than the paper base material contained in the laminate sheet for a lid body are classified into layers made of plastic and other layers, the mass of the paper base material is greater than the total mass of the layers made of plastic and the total mass of the other layers.
4. The laminate sheet for a lid body according to claim 1 , further comprising a printed layer between the water-resistant functional layer and the paper base material, and further comprising a gas barrier layer between the printed layer and the heat seal layer.
5. 2. The lid laminate sheet according to claim 1, wherein the paper base material is a coated paper having a coating layer on at least one surface thereof.
6. The ethylene-vinyl acetate copolymer contained in the heat seal layer has a glass transition temperature of -40°C or higher and a melting point within the range of 40 to 100°C.
7. 2. The lid laminate sheet according to claim 1, wherein the heat seal layer is a cured film of a coating film made of heat seal varnish.
8. The lid laminate sheet according to claim 1 , wherein the heat seal layer contains a secondary amide as the fatty acid amide-based additive.
9. 9. The lid laminate sheet according to claim 8, wherein the heat seal layer contains N-oleyl palmitamide as the secondary amide.
10. 2. The lid laminate sheet according to claim 1, wherein the heat seal layer has a thickness in the range of 2.5 to 5.5 [mu]m.
11. A lid comprising the laminate sheet for a lid according to any one of claims 1 to 10.
12. A food packaging container comprising a container body having an opening and a lid body as described in claim 11 that covers the opening, wherein the support layer is disposed between the paper base material and the internal space of the food packaging container.
13. 13. The food packaging container according to claim 12, wherein the container body has a flange around the opening, and the lid body is heat-sealed to the flange via the heat-seal layer.
14. 13. The food packaging container according to claim 12, wherein the internal space of the food packaging container is filled with a mixed gas containing oxygen gas, nitrogen gas, and carbon dioxide gas.
15. The food packaging container according to claim 12, wherein the food packaging container is a chilled food packaging container or a frozen food packaging container.
16. A packaged food comprising the food packaging container according to claim 12 and food contained in the food packaging container.
Citation Information
Patent Citations
Heat seal paper
JP2022011700A
Food packaging paper
JP2022048970A
Water-resistant paper and liquid container
JP2022130266A
Heat seal paper
JP2022175023A
heat seal paper
JP2023010963A